The effects of crıtıcal-thınkıng based ınstructıon on pre-servıce efl teachers’ crıtıcal thınkıng dısposıtıon level, englısh readıng self-effıcacy level, and englısh wrıtıng performance - Güner, Cansever (My University, 2015)
Bu çalışmanın amacı, eleştirel düşünme temelli öğretim yönteminin kullanımının Türk İngilizce öğretmen adaylarının eleştirel düşünme eğilim seviyeleri ile eleştirel okuma özyeterlik algılarına ve

yazma becerilerine etkilerini araştırmaktır. Çalışma aşağıdaki soruları yanıtlamayı amaçlamaktadır. Eleştirel düşünme temelli öğretim yöntemi İngilizce öğretmen adaylarının, 1. eleştirel düşünme eğilim seviyelerinde; 2. İngilizce eleştirel okuma özyeterlik algılarında; 3. İngilizce yazma becerilerinde anlamlı bir farklılığa neden olur mu? Çalışma verileri İstanbul, Türkiye’de bir devlet üniversitesinde eğitim alan 1. sınıf İngilizce öğretmen adaylarından toplanmıştır. Toplamda 61 katılımcıdan 31’i deney grubu olarak belirlemiş ve bu grup eleştirel düşünme temelli öğretim yönteminin kullanıldığı okuma/ yazma eğitimi almıştır. Kalan 30 katılımcı ise kontrol grubu olarak belirlenmiş ve bu grup geleneksel okuma/ yazma eğitimi almıştır. Bu çalışma 10 hafta sürmüş ve veriler Kaliforniya Eleştirel Düşünme Eğilim Ölçeği Türkçe versiyonu (Kökdemir, 2003), eleştirel okuma özyeterlik ölçeği (Küçükoğlu, 2008) ve öğretmen adaylarının tartışmacı tarzdaki komposizyonları, yoluyla elde edilmiştir. Elde edilen veriler, eleştirel düşünme temelli öğretim yönetiminin, öğretmen adaylarının eleştirel düşünme eğilimleri ile İngilizce eleştirel okuma özyeterlik seviyeleri ve İngilizce yazma becerilerinde istatistiki açıdan anlamlı farklılıklara yol açmadığını göstermiştir. ABSTRACT The present experimental study aims to find out the effects of critical thinking-based instruction on the critical thinking disposition, critical reading self-efficacy levels as well as L2 writing performance of Turkish pre-service teachers (PTs) of English. The following research questions are addressed: Will there be a statistically significant difference between the PTs who receive traditional reading and writing instruction and those who receive CT-based instruction in terms of their: 1.perceived critical thinking disposition level? 2.L2 critical reading self-efficacy level? 3.L2 writing performance? Data were collected from 61 freshman Turkish PTs of English studying at a state university in Istanbul, Turkey. With a total of 61 PTs, classes were randomly assigned as the control (N=30) and experimental group (N=31). The experimental group received critical thinking-based instruction whereas the control group received traditional reading/ writing instruction. The study lasted 10 weeks and data were collected by means of the Turkish version of the California Critical Thinking Disposition Inventory (Kökdemir, 2003), Critical Reading Self-Efficacy Scale (Küçükoğlu, 2008), and PTs’ argumentative essays. Results of the present study indicated that there was no statistically significant difference between the groups in terms of their perceived CT disposition and critical reading self-efficacy levels. L2 writing performance of the PTs in both groups did not vary to a statistically significant level as well. These findings indicate that the 10-week treatment did not contribute to overall perceived CT disposition and critical reading self-efficacy levels as well as L2 writing performance of the PT in the experimental group to a statistically significant level.
Keywords: Eğitim; İngilizce